Consumers' views on reporting of patient deterioration before the development of a consumer-activated response service. Issue 4 (August 2022) - Yu, Stephen; Thornton, Karleen; King, Lindy
ABSTRACT: Background: Services where patients and family members (consumers) are incorporated as responders in the reporting of patient deterioration is becoming a growing global strategy in healthcare. These services are designed to complement rapid response systems where reporting of patient deterioration is undertaken by health professionals such as nursing staff. Yet, research studies report limited consumer participation in the development of consumer-activated response services. The aim of this study was to investigate consumers' views on their reporting of patient deterioration before the development of a new consumer-activated response service in a healthcare organisation. Methods: A qualitative, focus group methodology was utilised. Ten consumers, previous patients or family members/carers from two acute hospitals, were interviewed. The focus group interviews were audio-recorded, transcribed and analysed using Attride-Stirling's (2001) thematic networks analysis framework. The COREQ criteria for reporting of qualitative research were used to guide this study (Tong et al., 2007). Findings: Three themes emerged: "reassurance is natural", "a response service is necessary" and "meaningful promotion is critical". Health professionals' reassurance motivated consumers' reporting of their concerns. A list of clinical symptoms of deterioration was not important to consumers. Patient advocates were seen as useful to consumers' decision-making to report deterioration. Routine messaging on the reporting process would encourage use of a consumer-activated response service. Conclusion: This study confirmed that consumers perceived the need for a consumer-activated response service. It also demonstrated the necessity of consumer involvement in the development of a response service so that the steps made sense to them. Consumers' perspectives were seen as integral to the development of educational materials related to the consumer-activated response service to maximise its effectiveness. The consumers' need for support and education to effectively utilise a consumer-activated response service was also highlighted. Nurses have a critical role in introducing and educating consumers on the consumer-activated response service when patients are in hospital.